2019
DOI: 10.3168/jds.2018-15265
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic milk replacers increase gastrointestinal permeability in healthy dairy calves

Abstract: Hypertonic milk replacers are commonly used in animal production systems and their effect on the gastrointestinal system of young animals is insufficiently studied. Total lactose inclusion or its partial replacement with dextrose increases intestinal osmotic pressure, which may compromise gastrointestinal barrier function. In this experiment, we investigated the effect of increased osmolality of calf milk replacer (CMR) on gastrointestinal permeability in 30 Holstein Friesian (n = 17) or crossbred (n = 13) bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…This could be associated with level of lactose, which increases the osmolality of CMR. This parameter can range from slightly hypertonic (just above 300 mOsm/ kg) to highly hypertonic (>450 mOsm/kg; Wilms et al, 2019). Hypertonic solutions have been associated with delayed abomasal emptying rate (Bell and Razig, 1973;Sen et al, 2006), which was shown to increase the incidence of gastrointestinal diseases in calves such abomasal bloat (Glenn Songer and Miskimins, 2005) and diarrhea (Foster and Smith, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be associated with level of lactose, which increases the osmolality of CMR. This parameter can range from slightly hypertonic (just above 300 mOsm/ kg) to highly hypertonic (>450 mOsm/kg; Wilms et al, 2019). Hypertonic solutions have been associated with delayed abomasal emptying rate (Bell and Razig, 1973;Sen et al, 2006), which was shown to increase the incidence of gastrointestinal diseases in calves such abomasal bloat (Glenn Songer and Miskimins, 2005) and diarrhea (Foster and Smith, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CMR has a higher ash content, particularly when it consists of mineral-rich Effect of energy source in calf milk replacer on performance, digestibility, and gut permeability in rearing calves 3995 dairy by-products. In addition, energy type and content in CMR may affect the osmolality of the solution (Wilms et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We did not monitor fecal consistency in this experiment; however, Amado et al (2019) indicated a better fecal consistency with HF versus HL CMR. Additionally, Wilms et al (2019) has shown that higher CMR osmolality may lead to higher gut permeability. With exchanging lactose for fat, CMR osmolality is reduced and would reduce gut permeability .…”
Section: Health Observationsmentioning
confidence: 99%
“…Calculated according to NRC (2001). 2 Roughly estimated according to the following equation: osmolality, mOsm/kg = [lactose, mmol/L] + [sodium, mmol/L] + [potassium, mmol/L] + [magnesium, mmol/L] + [calcium, mmol/L] + [phosphorus, mmol/L](Constable et al, 2009;Wilms et al, 2019).…”
mentioning
confidence: 99%